2021
DOI: 10.1177/2473974x211059111
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐Associated Macrophages in Vestibular Schwannoma and Relationship to Hearing

Abstract: Objective (1) Characterize the distribution of M1 and M2 macrophages in vestibular schwannomas by hearing status. (2) Develop assays to assess monocyte migration and macrophage polarization in cocultures with vestibular schwannoma cells. Study Design Basic and translational science. Setting Tertiary care center. Methods A retrospective chart review of 30 patients with vestibular schwannoma (VS) was performed. Patients were stratified into serviceable and unserviceable hearing groups. Immunohistochemistry for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In a meta-analysis by Hannah et al, inflammatory pathways were recognized as likely mediators of vestibular schwannoma hearing loss (22). The discovery of VS specific immune modulatory molecules such as tumor associated macrophages and inflammasomes can be linked to microinflammatory tumor behavior contributing to hearing loss (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis by Hannah et al, inflammatory pathways were recognized as likely mediators of vestibular schwannoma hearing loss (22). The discovery of VS specific immune modulatory molecules such as tumor associated macrophages and inflammasomes can be linked to microinflammatory tumor behavior contributing to hearing loss (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have demonstrated relationships between inflammatory cytokines, TAMs, and tumor growth in VS (2,6,9,12,28,56); however, the exact roles that M1 and M2 TAMs play in VS are still under debate. In a study performed by De Vries et al (5), the expression of protumorigenic M2 TAMs was linked to tumor growth in sporadic VS.…”
Section: Discussionmentioning
confidence: 99%
“…The exact role that M1 and M2 macrophages have in VS is still under investigation (5)(6)(7). Several investigations have identified associations between cytokines, macrophages, and clinical factors (i.e., hearing loss and tumor progression) in patients with VS (5,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The paraffin-embedded tissue blocks were retrieved for retrospective immunohistochemical analysis using a panmacrophage marker (CD68), an M1 marker (CD80), and an M2 marker (CD163). The combination of antibodies against CD80 and CD163 as M1 and M2 markers, respectively, has been previously utilized in multiple immunohistochemistry studies [ 33 , 34 , 35 ]. For quantification, at least four high-power fields (HPFs) were analyzed by a certified pathologist and manually counted in duplicates.…”
Section: Methodsmentioning
confidence: 99%